Total Synthesis of Maoecrystal P: Application of a Strained Bicyclic Synthon. (19th December 2017) - Su, Fan; Lu, Yandong; Kong, Lingran; Liu, Jingjing; Luo, Tuoping
Abstract: A new strategy was devised for the total synthesis of highly oxidized ent ‐kauranoids. A highly regio‐ and diastereoselective intermolecular Diels–Alder cycloaddition involving a diene embedded in a substituted bicyclo[4.1.0] skeleton was used to assemble all carbon centers but C17 of the target molecule at an early stage of the synthesis. Subsequent synthetic steps, including redox manipulations, SmI2 ‐mediated cyclization, and isomerization reactions, afforded the antitumor natural product maoecrystal P.